The peopling of the philippines - Virchow, Rudolf Ludwig Karl 1821-1902 (s.n., 1901)
Since the days when the first European navigators entered the South Sea, the dispute over the source and ethnic affiliations of the inhabitants of that extended and scattered island world has been unsettled. The most superficial glance points out a contrariety in external appearances, which leaves little doubt that here peoples of entirely different blood live near and among one another. And this is so apparent that the pathfinder in this region, Magellan, gave expression to the contrariety in his names for tribes and islands. Since dark complexion was observed on individuals in certain tribes and in defined areas, and light complexion on others, here abundantly, there quite exceptional, writers applied Old World names to the new phenomena without further thought. The Philippines set the decisive example in this. Fernando Magellan first discovered the islands of this great archipelago in 1521, March 16. After his death the Spaniards completed the circle of his discoveries. At this time the name of Negros was fixed, which even now is called Islas de los Pintados.